Study of clinical profile of acute lower respiratory tract infection in children aged 2 months to 5 years - M., Dhivyanarayani; V., Raju; P., Jeyachandran (International Journal of Contemporary Pediatrics, 2018)
Background: Acute respiratory infections are a leading cause of morbidity and mortality in under-five chil-dren in developing countries. Hence, the present study was undertaken to study the various risk factors, clinical profile and outcome of acute lower respiratory tract infections (ALRI) in children aged 2 months to 5 years. To study the risk factors associated with ALRI in these children. To ascertain the association of the various cultural practices prevalent in this area with ALRI. Methods: 100 ALRI cases fulfilling WHO criteria for pneumonia, in the age group of 2 months to 5 years were evaluated for potential risk factors, clinical profile and outcome as per a predesigned proforma in a rural medical college. Results: Socio-demographic risk factors like parental illiteracy, overcrowding, partial immunization and low socioeconomic status were potential risk factors; similarly, nutritional risk factors like early and late weaning, anemia, and malnutrition were associated with ALRI. Significant environmental risk factors were the use of biomass fuels, inadequate ventilation at home, and lack of separate kitchen. Conclusions: The present study has identified various socio-demographic, nutritional and environmental risk factors for ALRI which can be tackled by effective health education of the community and effective training of peripheral health personnel.